Longshot or Favorite: The Ending Effect in Investment Decisions - Wang, Qi; Zhang, JiaYuan; Xing, Cai (Frontiers in Psychology, 2021)
The ending effect describes the phenomenon that at the end of a series of repeated risky decision-making tasks, participants become more likely to engage in risk-taking behavior. Past research has suggested that the ending effect might be caused by a motivational shift induced by changes in time perception. Previous studies mainly tested this phenomenon in a binary decision-making setting (e.g., a decision-making task usually includes two alternatives). However, none of these prior studies included a safe option and risky options that differed in risk levels. To address this gap in knowledge, the present work replicated the ending effect in a repeated decision-making task that included both a safe option and risky options that differed in risk levels (N = 104). We found that at the end of the decision-making task, participants became more likely to engage in risk-taking and to favor the option with the highest risk. Further, we found that the investment likelihood and investment amount of high-risk options both increased significantly at the ending. We also found that the emotional motivation in the last round could predict the increased preference for high-risk at the ending. This work extends previous findings on the ending effect by adopting a more complex decision-making scenario and, more broadly, helps further our understanding of the psychological consequences of perceived endings.